Rahvuslikud üksused Punaarmee koosseisus ja välisriikide üksused NSV Liidu territooriumil Teise maailmasõja ajal [National military units in the Red Army and the units of foreign nations formed in the USSR during World War II] - Kaasik, Peeter (Eesti Sõjaajaloo Aastaraamat / Estonian Yearbook of Military History, 2015)
During World War II, the Soviet Union abandoned some of its pre‑war principles of assembling armed forces (including mixing nationalities in order to prevent the concentration of local inhabitants in the units located in the areas of their residence) and many units were formed based on ethnic composition. In addition to forming units from the nations of the former Baltic states, the Red Army formed similar units of the nations of north and south Caucasus, Central Asia and the Volga region, who were poorly integrated into Soviet society.However, Ukrainian and Belarusian soldiers were not formed into national units. Despite the fact that dozens of divisions and smaller national units had been formed from 1941 to 1943, it was not until February 1944 that a federal legislation was passed for regulating the formation of national units. National military units were an important means of propaganda. Forming national units in the complicated circumstances of the second half of 1941 was considered motivating for national minorities.(Longer version of the abstract is included in the article, starting from p 250.)